The Ghana Stock Exchange: Concentration, Diversification, Liquidity - Kumi, Eric (Division of Actuarial Science, 2014)
Analysts have foiled that concentration of portfolio weights affects portfolio risk. This is a unique feature in small markets whore they tend to be concentrated in few stocks and the Charm Sunk Exchange (GSE ) falls in that category. As a result portfolios based on the Ghana All Share index are highly concentrated. The risk in a portfolio is mainly attributed to Covariance and weighting structure. Enough cannot be done about the covariance structure but the weighting structure can be controlled since it depends mainly on investment choices. The weighting structure determines the degree of concentration of a portfolio. The term concentration refers to the extent to which portfolio weights skew away from equally weighted distribution of portfolio weights. As at September 2009, the Ghana All Share index has about five (5) of the total of thirty-five (3.5) in the index accounting for about 82.25% of the index weight. Concentration can be measured using the Herfindahl-Hirsclanan index (HHI) or Richard Roll measure (RRC). Diversification is (nmfirned with generation of returns from different sources. The iraditional method of measuring diversification has fallen short of vital, is usually expected hence the introduction of the new measure, portfolio diversification index or PDT. Liquidity measures the effect the quantity of stocks traded has on the market price of stocks. Liquidity varies from time to time; hence its importance as a source of risk for investors. The primary of fjective of this protect is to determine the significance of concentration in portiailio risk, particularly from the Ghanaian perspective. Furthermore, we will pleasing diversification ming the new measure and finally eml withshort review on liquidity in stock markets.